2008
DOI: 10.1088/0031-9155/53/23/005
|View full text |Cite
|
Sign up to set email alerts
|

In vivowater state measurements in breast cancer using broadband diffuse optical spectroscopy

Abstract: Structural changes in water molecules are related to physiological, anatomical and pathological properties of tissues. Near infrared (NIR) optical absorption methods are sensitive to water, however detailed characterization of water in thick tissues is difficult to achieve because subtle spectral shifts can be obscured by multiple light scattering. In the NIR, a water absorption peak is observed around 975nm. The precise NIR peak shape and position is highly sensitive to water molecular disposition. We introdu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
105
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(113 citation statements)
references
References 70 publications
(111 reference statements)
6
105
0
Order By: Relevance
“…18 Previous reports using diffuse optical spectroscopy have suggested that malignant tumors have reduced lipid (∼20%) and increased water (>50%) contents compared to normal breast tissue. [19][20][21][22] In addition, other reports suggest a positive correlation between increased tissue water content and carcinogenesis. 23 Although the water content in benign lesions may vary significantly depending on the type of lesions, 24 the quantitative information of lesion composition can be used to improve the positive predictive value for cancer detection.…”
Section: Introductionmentioning
confidence: 99%
“…18 Previous reports using diffuse optical spectroscopy have suggested that malignant tumors have reduced lipid (∼20%) and increased water (>50%) contents compared to normal breast tissue. [19][20][21][22] In addition, other reports suggest a positive correlation between increased tissue water content and carcinogenesis. 23 Although the water content in benign lesions may vary significantly depending on the type of lesions, 24 the quantitative information of lesion composition can be used to improve the positive predictive value for cancer detection.…”
Section: Introductionmentioning
confidence: 99%
“…4 Leff et al 5 recently reviewed DOT breast tumor contrasts in Hb t and StO 2 . Some disagreements remain in the diffuse optics community about which optically measured parameters are the most important indicators of malignancy; recent work, for example, on water 6 and collagen 7 has opened up additional possibilities.…”
Section: Introduction Ia Diffuse Optics and Automated Cancer Diamentioning
confidence: 99%
“…Both the transmitted light (transmission or transillumination spectroscopy) and the diffusely reflected radiation (reflectance or backscattering spectroscopy) are detected. [179,199,200,203,204,211] techniques. The near IR spectroscopy makes use of the same principles and the same methods of data recording, as the modern optical imaging methods, based on the detection of diffusely scattered light, and in this sense is their direct predecessor.…”
Section: Methods Based On the Detection Of Diffusely Scattered Lightmentioning
confidence: 99%